Presidential Decree-law No. 7 of the year 2015 On Amending Certain Provisions of The Child Law Promulgated by Law No. 12 of the year 1996 = قرار رئيس جمهورية مصر العربية بالقانون رقم 7 لسنة 2015 بتعديل بعض أحكام قانون الطفل الصادر بالقانون رقم 12 لسنة 1996 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic